PENGARUH CR, ROA, ROE DAN EPS TERHADAP RETURN SAHAM PADA PERUSAHAAN REAL ESTATE AND PROPERTY. - Yohana Agusrina; Sulistyorini; Novasari, Linda (ITB AAS Indonesia Surakarta, 2025)
ABSTRACT The results of research that examine the effect of the current ratio, Return On Asset (ROA), Return On Equity (ROE) Earning per Share (EPS) on stock returns. The population in this study uses property and real estate companies listed on the Indonesia Stock Exchange (IDX), which continuously publish financial reports and annual reports for the period 2020-2023. The sample in this study used a purposive sampling method, the sample obtained was 20 companies that were consistently listed on the IDX in 2020-2023, so that 60 observational data were obtained. The data collection method is done by means of documentation. Data collected were analyzed with multiple regression techniques and hypothesis testing. The results of this study simultaneously showed the results of this study showed that size, CR had a positive and not significant effect, ROA had a positive and significant effect, ROE has a negative and significant effect, EP has a positive and insignificant effect on stock returns.